Soft wood grafting in clove (Syzygium aromaticum (L.) Merr. & Perry) on related species - KRISHNAMOORTHY, P A MATHEW, J REMA, B (Journal of Spices and Aromatic Crops, 1999)
The influence of root stocks on size of the tree, precocity, and reaction to biotic and abiotic stresses is well known, In clove (a major tree spice of India), harvesting is laborious and expensive, and the tree is susceptible to many pests and diseases, which infest the basal region of the stem and roots, To overcome these problems efforts were made at the Indian Institute of Spices Reasearch, Calicut, during September 1996 to study the feasibility of grafting clove on various related species,